QARDHUL HASAN SEBAGAI WUJUD PELAKSANAAN CSR DAN KEGIATAN FILANTROPI LEMBAGA KEUANGAN SYARIAH UNTUK PEMBERDAYAAN MASYARAKAT - Muh Awal Satrio (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2015)
The escalating social andeconomic problems brought about by globalization have raised new questions as well as expectations about corporate governance,ethical and social responsibilities. Consequently, corporate social responsibility (CSR) as a part of phylanthropy’s activities has emerged and developed rapidly as a fieldof study. The Islamic financial institution has special program , Qardhul Hasan, that is perceived as the same as corporate social responsibility. The main objectiveof thispaperis to elaborate corporate social responsiblity from Islamic’s view and to evaluate wether the Qardhul Hasan is the same as corporate social responsibility in business entity.